Age-adjusted impact of prior COVID-19 on SARS-CoV-2 mRNA vaccine response - Nakagama, Sachie; Nakagama, Yu; Komase, Yuko; Kudo, Masaharu; Imai, Takumi; Tshibangu-Kabamba, Evariste; Nitahara, Yuko; Kaku, Natsuko; Kido, Yasutoshi (Frontiers in Immunology, 2023)
More people with a history of prior infection are receiving SARS-CoV-2 vaccines. Understanding the level of protection granted by ‘hybrid immunity’, the combined response of infection- and vaccine-induced immunity, may impact vaccination strategies through tailored dosing. A total of 36 infected (‘prior infection’) and 33 SARS-CoV-2 'naïve' individuals participated. Participants provided sera six months after completing a round of BNT162b2 vaccination, to be processed for anti-spike antibody measurements and the receptor binding domain-ACE2 binding inhibition assays. The relationships between antibody titer, groups and age were explored. Anti-spike antibody titers at 6 months post-vaccination were significantly higher, reaching 13- to 17-fold, in the ‘prior infection’ group. Semi-log regression models showed that participants with ‘prior infection’ demonstrated higher antibody titer compared with the ‘naïve’ even after adjusting for age. The enhancement in antibody titer attributable to positive infection history increased from 8.9- to 9.4- fold at age 30 to 19- to 32-fold at age 60. Sera from the ‘prior infection’ group showed higher inhibition capacity against all six analyzed strains, including the Omicron variant. Prior COVID-19 led to establishing enhanced humoral immunity at 6 months after vaccination. Antibody fold-difference attributed to positive COVID-19 history increased with age, possibly because older individuals are prone to symptomatic infection accompanied by potentiated immune responses. While still pending any modifications of dosing recommendations (i.e. reduced doses for individuals with prior infection), our observation adds to the series of real-world data demonstrating the enhanced and more durable immune response evoked by booster vaccinations following prior infection.